Circular RNA circNUP214 Modulates the T Helper 17 Cell Response in Patients With Rheumatoid Arthritis - Peng, Huiyong; Xing, Jie; Wang, Xuehua; Ding, Xiangmei; Tang, Xinyi; Zou, Junli; Wang, Shengjun; Liu, Yingzhao (Frontiers in Immunology, 2022)
Circular RNAs (circRNAs) are important transcriptional regulators of genome expression that participate in the pathogenesis of human diseases. Mechanistically, circRNAs, as competitive endogenous RNAs (ceRNAs), can sponge microRNAs (miRNAs) with miRNA response elements. A previous study identified that hsa_circ_0089172 (circNUP214) is abnormally expressed in Hashimoto’s thyroiditis. However, the role of circNUP214 in rheumatoid arthritis (RA) remains unclear. In total, 28 RA patients and 28 healthy controls were enrolled in this study. We found that circNUP214 is an abundant and stable circRNA in RA patients that can potentially differentiate RA patients from healthy subjects. Additionally, the elevated levels of IL-23R positively correlated with circNUP214 expression. The knockdown of circNUP214 resulted in the reduction of IL-23R at both transcriptional and translational levels in human CD4+ T cells. The proportion of circulating Th17 cells and the transcript levels of IL-17A were increased in RA patients and were both positively correlated with IL-23R expression. Moreover, positive correlations between the transcript levels of circNUP214 and the percentage of Th17 cells and the transcript levels of IL-17A were observed in RA patients. The downregulation of circNUP214 decreased the proportion of Th17 cells and the transcript levels of IL-17A in vitro. Furthermore, circNUP214 functioned as a ceRNA for miR-125a-3p in RA patients. Taken together, our results indicate that elevated levels of circNUP214 contribute to the Th17 cell response in RA patients.